The History of the AutoChemist®: From Vision to Reality - Peterson, H. E.; Jungner, I. (Yearbook of Medical Informatics, 2014)
Objectives: This paper discusses the early history and development of a clinical analyser system in Sweden (AutoChemist, 1965). It highlights the importance of such high capacity system both for clinical use and health care screening. The device was developed to assure the quality of results and to automatically handle the orders, store the results in digital form for later statistical analyses and distribute the results to the patients’ physicians by using the computer used for the analyser.Results: The most important result of the construction of an analyser able to produce analytical results on a mass scale was the development of a mechanical multi-channel analyser for clinical laboratories that handled discrete sample technology and could prevent carry-over to the next test samples while incorporating computer technology to improve the quality of test results. The AutoChemist could handle 135 samples per hour in an 8-hour shift and up to 24 possible analyses channels resulting in 3,200 results per hour. Later versions would double this capacity. Some customers used the equipment 24 hours per day.Conclusions: With a capacity of 3,000 to 6,000 analyses per hour, pneumatic driven pipettes, special units for corrosive liquids or special activities, and an integrated computer, the AutoChemist system was unique and the largest of its kind for many years. Its follower – The AutoChemist PRISMA (PRogrammable Individually Selective Modular Analyzer) – was smaller in size but had a higher capacity. Both analysers established new standards of operation for clinical laboratories and encouraged others to use new technologies for building new analysers.
Keywords: History of medical informatics; high capacity clinical analyser system; discrete sample technology; medical information technology; large scale laboratory automation; mass analysis equipment for health screening.